Does it pay to attend an elite private college? Cross-cohort evidence on the effects of college type on earnings. - Brewer, Dominic J.; Eide, Eric R.; Ehrenberg, Ronald G. (Journal of Human Resources)
Although a substantial and rising labor market premium is associated with college attendance in general, little is known about how this premium varies across institutions of different types and across time. In this paper we explicitly model high school students' choice of college type (characterized by selectivity and control) based on individual and family characteristics (including ability and parental economic status) and an estimate of the net costs of attendance. We estimate selectivity-corrected outcome equations using data from both the National Longitudinal Study of the High School Class of 1972 and High School and Beyond, which permit us to determine the effects of college quality on wages and earnings and how this effect varies across time. Even after controlling for selection effects, strong evidence emerges of a significant economic return to attending an elite private institution, and some evidence suggests this premium has increased over time. Reprinted by permission of the publisher.